Deploying strategic resources: comparing members of farmer cooperatives to non-members in sub-Saharan Africa. Issue 3 (3rd July 2017) - Olthaar, Matthias; Noseleit, Florian
Abstract: Primary producers in global value chains, like any other firm, aim for entrepreneurial success through deploying strategic resources, collective action, strategic intent, and a supportive institutional environment. In the current article, we analyze the extent to which members of farmer cooperatives in Ethiopia succeed in deploying strategic resources. We find that non-members utilize resources more efficiently and that the potential for collective action is not realized. The potential for collective action remains unrealized due to the institutional environment. We suggest pathways for further research.